2019
DOI: 10.3390/molecules24020327
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, In Silico, and In Vitro Evaluation of Long Chain Alkyl Amides from 2-Amino-4-Quinolone Derivatives as Biofilm Inhibitors

Abstract: Infection from multidrug resistant bacteria has become a growing health concern worldwide, increasing the need for developing new antibacterial agents. Among the strategies that have been studied, biofilm inhibitors have acquired relevance as a potential source of drugs that could act as a complement for current and new antibacterial therapies. Based on the structure of 2-alkyl-3-hydroxy-4-quinolone and N-acylhomoserine lactone, molecules that act as mediators of quorum sensing and biofilm formation in Pseudom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…A series of 1-amino-2-aryliden- amine-1,2-(dicyano)ethenes as antifungal agents effective against yeasts were reported by Bettencourt et al [17]. Several synthesized long chain alkyl amides of 2-amino-4-quinolones demonstrated a high inhibition of biofilm formation of Pseudomonas aeruginosa [18].…”
mentioning
confidence: 99%
“…A series of 1-amino-2-aryliden- amine-1,2-(dicyano)ethenes as antifungal agents effective against yeasts were reported by Bettencourt et al [17]. Several synthesized long chain alkyl amides of 2-amino-4-quinolones demonstrated a high inhibition of biofilm formation of Pseudomonas aeruginosa [18].…”
mentioning
confidence: 99%
“…On the other hand, both compounds 2 and 3 were able to suppress swarming motility in P. aeruginosa, while the full-length alkyl chain compound 1 did not. Espinosa-Valdés et al have previously shown that shortening the alkyl chain of 2-amino-4-quinolone (AQ) derivatives can lead to loss of activity against P. aeruginosa biofilms [48]. Several studies have shown that a wide range of structural modifications in AQ analogues are capable of enhancing or maintaining anti-biofilm, anti-swarming and anti-pyocyanin production activities [30,[48][49][50][51][52], suggesting promiscuity within the framework from an antagonistic perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively few existing studies on the interspecies activity of the AQ signalling framework and its ability to control the virulence profiles of other microbes means that there is currently no concise understanding with respect to the possible ligand–receptor interactions that underpin AQ-mediated interspecies communication. While compounds with a shorter alkyl chain have been shown to bind more effectively to the LasR quorum sensing receptor protein than even the agonist signal molecule [ 48 ], there is no evidence in this current study of receptor binding at the interspecies level [ 44, 61 ]. Co-infection between P. aeruginosa and S. aureus promotes changes in genetic regulation resulting in a conversion of essential genes to expendable genes in co-infection, as observed in a murine wound model [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…At a concentration of 20 M, the two most effective compounds (a) and (b) likewise condensed the creation of pyocyanin by between 62.6 and 68.2%. None of the investigated substances had an impact on bacterial growth, indicating that the derivatives' activity might have been modulated by QS 21 .…”
Section: Anti-virulence Activitymentioning
confidence: 95%